TRENDS IN THE CONCEPTUALIZATIONS OF TRENDS IN THE SECOND LANGUAGE COMPOSING STRATEGIES: A CRITICAL ANALYSIS - Manchon, Rosa M. (International Journal of English Studies, 2001)
This paper presents a review of empirical studies on second language (L2) composing strategies from the perspective of the conceptualizations that guide research in the field. The study of strategies is first contextualized in psychology, in the study of L2 acquisition and in the L2 writing process-oriented research. It is then suggested that definitions of strategies fall into two main groups, referred to in the paper as the broad and narrow conceptualizations, respectively. After reviewing and critically assessing the empirical studies carried out within these two paradigms, it is concluded that if research in the field aims at contributing to theory building, it seems advisable to engage in more theoretically-grounded and methodologically-principled enquiry into composing strategies. Some suggestions for a future research agenda are advanced.